The development of XML document retrieval using query weighting / Fauziah Mat Saat - Mat Saat, Fauziah (2005)
Query is one of the processes involved in information retrieval in order to obtain the retrieved documents. Query is importance in information retrieval because it will affect the retrieved documents. The poor fomiulated queries will lead to the poor document retrieval such as the retrieved document might be too large or too small and no provision for ranking documents. There are many techniques that we can use to process the user query and these different kinds of techniques will give a different result for documents retrieval. One of the techniques is using query weighting algorithm which is either the system will calculate the weight of the importance words or the user itself will give a weight to the importance words. This research is focus on developing an XML documents retrieval using a query weighting algorithm in order to retrieve FTMSK official letter. This technique has been successfully tested and it proves that query weighting technique is very effective in XML document retrieval. Keywords: Query Weighting, XML Documents Retrieval, Query.